ANALISIS SEMIOTIKA KOMUNIKASI PADA BARONG BRUTUK DI DESA TRUNYAN KINTAMANI BANGLI - Komang Dyah Setuti; I Wayan Wastawa; I Nyoman Ananda (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
Barong Brutuk is an ancient sacred art that our ancestors passed down way before Hinduism was introduced to Indonesia. It is still practiced and observed today by the people of Trunyan Village in Kintamani Bangli. This research is conducted in order to know (1) the symbols that used in Barong Brutuk, (2) the communication function of Barong Brutuk, (3) the meaning of communication semiotic from sender to the receiver of message. This research is a qualitative research, that using the theory of communication semiotic, theory of religious communication, and theory symbolic interaction. Analytical techniques with hermeneutic analysis. Based on the results of the analysis and discussion, it came to our conclusion that the symbols used in Barong Brutuk in Trunyan Village consist of mask (tapel), kraras leaves, and whip. The mask symbolizes the meeting of the god Trunyan with his future consort, it is interpreted as the meeting of man and women led to believe to be the start of human life. The kraras leaves symbolizes the soil fertility, protecting the environment and the prevention of natural disasters. The belief of self-sacrifice as a means of healing disease, the hope of obtaining offspring is symbolized by the whip. Barong Brutuk has many purposes and uses such as communication, as a means of pleasure, and entertainment for the community, it also reflects on the Trunyan Villages identity as an integrative tool. It’s a method of healing, education and integration during a time of chaos.